Postoperative risk stratification in oral squamous cell carcinoma. Issue 4 (May 2020) - McMahon, J.D.; Pitts, R.; Isbister, J.; Aslam-Pervez, B.; James, A.; McLellan, D.; Wright, S.; Wales, C.J.; McCaul, J.; Thomson, E.; Ansell, M.J.; Hislop, W.S.; et al.
Abstract: Postoperative prognostic stratification using the Union for International Cancer Control (UICC) TNM 8th edition staging rules (UICC 8) may identify additional groups of patients who could benefit from adjuvant radiotherapy. Currently, selection for such treatment is not based on all known prognostic factors, and their relative importance may vary depending on the overall risk category. The objective of this study therefore was to evaluate these possibilities. We retrospectively studied 644 patients who had surgery with curative intent for oral squamous cell carcinoma (OSCC) between March 2006 and February 2017. The outcomes of interest were disease-specific survival (DSS) and locoregional recurrence (LRR). Patients were re-staged according to the UICC 8 staging rules. Putative clinical and pathological prognostic variables were evaluated and hazard ratios estimated. Regression analysis was done to identify independent prognostic factors, and iterative analyses identified clinically-relevant risk categories with a minimum of residual prognostic variables. The significance of recognised pathological prognostic factors differed according to the overall risk category. An intermediate risk group comprising patients with pN1 disease as well those with pT3 disease solely on the basis of a depth of invasion (DOI) of more than 10 mm, was identified. A trial to evaluate the benefit or otherwise of adjuvant radiotherapy in this group is now required. Individual prognostic risk factors should be considered within the context of the overall risk category in patients with OSCC.